2019
DOI: 10.14807/ijmp.v10i1.825
|View full text |Cite
|
Sign up to set email alerts
|

ISO 14001 and international trade

Abstract: The purpose of this paper is to study potential association between international trade and ISO 14001 certification. The study is based upon a search conducted by International Organization for Standardization (ISO) performed in 2013, which includes responses from 110 countries in 11 languages. At this time, among all topics from the research, the variables studied were motivations for implementation and the benefits achieved. These data were crossed with features of international business trade to identify it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…These benefits have resulted in the specification of multiple positive benefits or outcomes following ISO 14001 certification. On the contrary, other studies concluded that the certification process did not result in any significant changes in organizational performance or practices [76,77]. The French Standardization Association (AFNOR) introduced a study researched by the Paris Dauphine University entitled "Performance des organizations".…”
Section: Discussionmentioning
confidence: 99%
“…These benefits have resulted in the specification of multiple positive benefits or outcomes following ISO 14001 certification. On the contrary, other studies concluded that the certification process did not result in any significant changes in organizational performance or practices [76,77]. The French Standardization Association (AFNOR) introduced a study researched by the Paris Dauphine University entitled "Performance des organizations".…”
Section: Discussionmentioning
confidence: 99%
“…At the end of 2015, a new edition of the Environmental Management Standard ISO 14001 was issued [16]. This edition has been developed to be suitable with the complexities of the labor market these days [17].…”
Section: The Iso 14001 Requirementsmentioning
confidence: 99%
“…Environmental management systems (EMS) are designed to help organizations "identify, manage, monitor and control their environmental issues in a holistic manner" [1]. The International Organization for Standardization (ISO) 14001 certification system, established in 1996 and updated in 2004 and 2015 [2], has rapidly become the most-utilized EMS worldwide [3]. ISO 14001 certification does not specify particular environmental goals (e.g., reduction of certain pollutants, reduction of energy consumption, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Second, many studies have examined the benefits or outcomes of EMS certification, both for the organizations and for the environment, the extent to which certification results in positive outcomes remain controversial, however. Many studies have found multiple positive benefits or outcomes following ISO 14001 certification, but other studies have found that the certification process did not lead to any significant changes in organizational performance or practices [2,5]. Third, research on the KFS for EMS certification is more recent and less well-developed than research on EMS certification outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation